2020
DOI: 10.1371/journal.pmed.1003090
|View full text |Cite|
|
Sign up to set email alerts
|

National and regional prevalence of posttraumatic stress disorder in sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Background People living in sub-Saharan Africa (SSA) are disproportionately exposed to trauma and may be at increased risk for posttraumatic stress disorder (PTSD). However, a dearth of population-level representative data from SSA is a barrier to assessing PTSD. This manuscript sought to calculate pooled PTSD prevalence estimates from nationally and regionally representative surveys in SSA. Methods and findings The search was conducted in PubMed, Embase, PsycINFO, and PTSDpubs and was last run between October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 112 publications
4
50
2
Order By: Relevance
“…Despite the fact that PTSD may be higher in conflictaffected LMICs, and at least as prevalent in non-conflict LMIC settings, as compared to HICs [33][34][35][36], many LMICs have extremely limited mental health services making implementation of EBIs challenging [37,38]. Low-income countries have less than one mental health provider per 100,000 people (compared to more than 50 in HICs), and almost all mental health services in lowincome countries are provided in hospitals in large cities, with virtually no care available in rural areas [38][39][40].…”
Section: Introductionmentioning
confidence: 90%
“…Despite the fact that PTSD may be higher in conflictaffected LMICs, and at least as prevalent in non-conflict LMIC settings, as compared to HICs [33][34][35][36], many LMICs have extremely limited mental health services making implementation of EBIs challenging [37,38]. Low-income countries have less than one mental health provider per 100,000 people (compared to more than 50 in HICs), and almost all mental health services in lowincome countries are provided in hospitals in large cities, with virtually no care available in rural areas [38][39][40].…”
Section: Introductionmentioning
confidence: 90%
“…The last two decades have seen a rise in research on PTEs and PTSD, in particular, in non-Western low-and middle-income countries (LMICs) that has found comparable rates with high-income Western settings (Atwoli et al, 2015;Koenen et al, 2017;Rasmussen et al, 2014). For example, in sub-Saharan Africa a recent review found that pooled prevalence rates for PTSD were 22% for individuals across 10 sub-Saharan African countries, with areas exposed to war or armed conflict reporting prevalence rates closer to 30% (Ng et al, 2020).…”
Section: Illness In a Non-western Setting: Data From Rural Ethiopiamentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a significant worldwide health concern, and is highly prevalent in sub-Saharan Africa [ 1 ]. A recent meta-analysis showed that the pooled prevalence of probable current PTSD across 10 countries in sub-Saharan Africa was 22% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%